Genome-Wide Association Analysis of Sweet Pepper (Capsicum annuum) Based on Agronomic Traits Using PepperSNP50K - Yaolong Wang; Entong Li; Jiawei Lu; Jing Wang; Qiaolu Zang; Yanping Liang; Ruxia Tian; Changwei Zhang; Fangling Jiang; Yan Cheng (Plants)
As one of the most important vegetables globally, peppers have garnered significant attention from breeders due to their diverse agronomic traits, including plant type, leaf shape, and maturity. Understanding the genetic mechanisms underlying these traits is crucial for systematic advancements in sweet pepper breeding. In this study, leveraging the PepperSNP50K liquid breeding chip, we conducted a comprehensive analysis of horticultural traits and genetic diversity using sweet pepper germplasm samples. Initially, the sweet pepper populations were analyzed using SNP-based liquid chip technology. Subsequently, phenotypic surveys were performed on 217 sweet pepper samples, and the collected phenotypic data were integrated with SNP markers to conduct a genome-wide association study (GWAS) of key agronomic traits. Among the 25 horticultural traits evaluated, 11 exhibited significant associations with 54 SNP polymerization regions and 193 candidate genes. These findings provide a robust foundation for the utilization of sweet pepper germplasm resources and the development of new, improved varieties. Furthermore, in this study, we identified Caz06g05770 (Lycopene beta-cyclase) as a candidate gene responsible for the color of mature ripe fruits. This research not only enhances our understanding of the genetic basis of sweet pepper traits but also offers a practical roadmap for advancing breeding programs and boosting agricultural productivity. By bridging the gap between genetic research and practical breeding applications, this study paves the way for the development of high-yield, high-quality sweet pepper varieties tailored to meet the growing demands of global agriculture.